Les pronoms : quelques problèmes de délimitation de la catégorie - Jérôme Puckica (Corela)
This article deals with the pronoun word-class, its definition and the distinction between pronouns and determiners. It first examines the traditional and etymological definition of the pronoun as a word put ‘instead of a noun’, a definition which is hardly appropriate for various reasons, beginning with the fact that only some pronouns can be used anaphorically. A redefinition of the pronoun class is then proposed as a closed class of grammatical nouns that do not take determiners and whose central members are typically used anaphorically or deictically. The third part of the article focuses on the distinction between pronouns and determiners and related issues such as nominal ellipsis. It is argued that determiners are also grammatical nouns, yet that the distinction between determiners and pronouns is motivated and descriptively useful in at least some cases, most particularly with regard to the articles and the personal pronouns.